Ab Initio Magnetic Properties Simulation of Nanoparticles Based on Rare Earth Trifluorides REF3 (RE = Tb, Dy, Ho) - Pulat Saidakhmetov; Irina Piyanzina; Amina Faskhutdinova; Oleg Nedopekin; Gulmira Adyrbekova; Gulzagira Baiman; Zhamilya Suyerkulova; Irina Romanova (Crystals, 2023)
Recently, nanoparticles based on rare earth fluorides have been widely investigated due to their possible medical and spintronic applications, where it is desirable to know the magnetic moment volume distribution. However, this feature is hard to find out from the experiments, so we employ ab initio spin-polarized calculations for this purpose in order to find out the tendencies and common features in three different compounds. In the present work, the nanoparticles of dipole magnets with different sizes, namely TbF3, DyF3 and HoF3, were simulated, and optimized structures were found. We present the optimized structures for the particles with various sizes, as well as for slabs constructed from same compounds. Lastly, for optimized geometries, the analysis of magnetic moments’ distribution over the nanoparticles and slabs volume was performed.